2018
DOI: 10.1111/iej.12912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral premedication on the anaesthetic efficacy of inferior alveolar nerve block in patients with irreversible pulpitis – A systematic review and network meta‐analysis of randomized controlled trials

Abstract: This systematic review (SR; PROSPERO database: CRD42017075160) and network meta-analysis (NMA) identified the most effective oral premedication for anaesthetic success of inferior alveolar nerve blocks (IANB) in cases of irreversible pulpitis. Medline and Ebscohost databases were searched up until 10/2017. Randomized controlled trials (RCT) studying the effect of oral premedication, alone or in combination, on the success of IANB for cases of irreversible pulpitis, compared to placebo or other oral premedicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
1
24
0
3
Order By: Relevance
“…One of the main problems faced regarding antibiotic usage is the lack of clear guidelines for their prescription [31], which was the case in the past. But recently, new guidelines have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main problems faced regarding antibiotic usage is the lack of clear guidelines for their prescription [31], which was the case in the past. But recently, new guidelines have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the authors concluded that the type, volume and supplemental buccal injection did not have any influence. A recent meta-analysis made a different conclusion compared to others and favored the use of oral premedication with dexamethasone, NSAIDs or tramadol; yet drew attention to the necessity of more trials [86].…”
Section: Discussionmentioning
confidence: 99%
“…). Example 5b : ‘Quality of the included studies was appraised by the revised Cochrane risk of bias tool for randomized trials’ (Pulikkotil et al . ).…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%